The effect of institutional distance on cross-border merger and acquisition time to completion: an empirical analysis of European Union deals - Santos, Célia Maria Ferraz dos (2018)
Cross-border merger and acquisitions (CBM&As) have extensively been used as a favorite entry mode in foreign markets, rapidly providing resources, competencies and local intelligence without risk of facing the liability of foreignness, or the burden of starting a greenfield investment. Studies indicate that greater institutional distance increases the costs of doing business in a foreign country, because it is associated with greater uncertainty and non-familiarity with the local environment. Besides that, prolonged duration of the M&A process has negative consequences for target and acquirer firms and bear significant costs for both parties. However, until so far, the studies regarding the effect of institutional distances on time to completion of a CBM&A deal are scarce. My theoretical model speculates on the effect of institutional distances (Political, Economic, Administrative and Cultural) in CBM&As time to completion. I further propose that European Union membership, of both target and acquirer countries, moderates the effect of institutional distances on CBM&As time to completion. The hypotheses are tested using a sample of 2,110 CBM&A deals that occurred during 2011 in European Union. On one hand, the results suggest that Political and Cultural distance have a positive effect on the time hiatus between announcement and completion of a CBM&A deal. On the other hand, the results suggest that European Union membership does moderate the effect of Economic and Administrative distance in CBM&A time to completion.